2018
DOI: 10.1002/app.46766
|View full text |Cite
|
Sign up to set email alerts
|

Conductive, antibacterial, and electromagnetic shielding silver‐plated cotton fabrics activated by dopamine

Abstract: A two-step method was developed in this article to fabricate conductive silver-plated cotton fabrics, imparting them with antibacterial and electromagnetic shielding properties. Cotton fabric was firstly functionalized by a spontaneous polymerization of dopamine, which acted as an activation and adsorption layer to initiate the following silver plating through the catechol and indole functional groups. The chemical composition of the functional cotton fabric was investigated by X-ray photoelectron spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…[ 32–34 ] It was observed that the diffraction peaks of cotton @ PDA are practically similar to that of pristine cotton textile, which reveals that the treatment of PDA has no effect on the crystal structure of substrate. [ 35 ] While the sample coated by 100 ALD cycle ZnO was found to possess the wurtzite ZnO phase with all diffraction peaks well indexed to hexagonal phase (JCPDS No. 36–1451).…”
Section: Resultsmentioning
confidence: 99%
“…[ 32–34 ] It was observed that the diffraction peaks of cotton @ PDA are practically similar to that of pristine cotton textile, which reveals that the treatment of PDA has no effect on the crystal structure of substrate. [ 35 ] While the sample coated by 100 ALD cycle ZnO was found to possess the wurtzite ZnO phase with all diffraction peaks well indexed to hexagonal phase (JCPDS No. 36–1451).…”
Section: Resultsmentioning
confidence: 99%
“…68 Mao et al used PDA to reduce silver ions for the preparation of AgNP/cotton fabrics, which possessed high-effective antibacterial and shielding properties (55–95 dB). 70 Based on triethanolamine reduction, Shao et al reported a simple and economical method for the fabrication of an AgNP/nonwoven polypropylene (PP) membrane with the maximum SE value of 71.6 dB. 75…”
Section: Design and Preparation Of Sliver/polymer Based Emi Shielding...mentioning
confidence: 99%
“…Ghosh et al developed AgNP-coated fabrics with an SE of 30.07 dB in the X-band frequency range and effective bactericidal activity against E. coli . 220 Many antibacterial silver-based EMI shielding materials, such as AgNP/cotton fabrics, 70 AgNP/PAN fibers, 95 and AgNP/PPS composites, 39 have been introduced in the previous paragraph. However, AgNWs are considered the best candidates for enhancing the EMI shielding ability of CPCs despite the fact that they are powerless in killing bacteria.…”
Section: Multi-functionalization Of Silver/polymer Shielding Materialsmentioning
confidence: 99%
“…The silver-coated polyimide fiber has good antibacterial activity, high conductivity and reflectivity, the electrical resistance is only 1.5 Ω and the reflectivity reaches 95%. In addition, there have been studies on silver-plated cotton fiber [16,17], kapok fiber [18], polyurethane fiber [19], ultrahigh molecular weight polyethylene fiber [20], polyacrylonitrile nanofibers [21], polyester fiber [22][23][24] and glass fiber [24,25] by employing dopamine surface modification. Regarding aramid fibers, Wang et al [26] prepared silver-plated aramid staple fiber by employing dopamine modification, which has excellent ultrasonic stability, but the staple fiber form limits the practical application of aramid, and also lacks the washing fastness test under standard conditions.…”
Section: Introductionmentioning
confidence: 99%